Sustainable Institutional Performance Development Through Marketing Capabilities: Evidence from the Banking Sector - AL-Ghaswyneh, Odai Falah Mohammad (European Journal of Sustainable Development, 2025)
This study investigates the connection between marketing capabilities and the enhancement of Sustainable Institutional Performance development within Saudi banks. Employing a descriptive analytical approach, the research relied on secondary sources for theoretical data and utilized a questionnaire to gather empirical data from 157 employees working in Saudi banks. A total of 137 completed questionnaires were deemed valid for analysis, reflecting a high response rate of 87.25%. The collected data were processed using the Statistical Package for the Social Sciences (SPSS) to examine the proposed hypotheses. The findings reveal a strong presence of practices associated with both key variables—marketing capabilities and Sustainable Institutional Performance development—as well as a significant positive relationship between them. The strongest relationships between the ability to manage marketing communications as one of the dimensions of marketing capabilities and institutional performance, the least relationships were between the ability to manage distribution channels as one of the dimensions of marketing capabilities and institutional performance. In addition to the existence of a significant impact of all dimensions of marketing capabilities on Sustainable Institutional Performance development. The study recommended enhancing customer understanding by conducting advanced market studies and research using data analysis techniques to understand more deeply the needs of customers and their future directions, in addition to activating marketing strategies through data derived from market research. Strictly targeted marketing campaigns are designed to provide many banking services. There is also a need to leverage technology and artificial intelligence tools to improve the accuracy of marketing forecasts and make decisions supported by advanced data and analytics, encourage a culture of innovation and creativity by motivating employees to present new ideas, develop banking products and provide innovative services that meet customer aspirations and outperform competitors. Keywords: Marketing Capabilities – Institutional Performance – Saudi Banks